Antenatal diagnostic dilemma in a pseudodominant pedigree with lamin‐B receptor (LBR)‐related regressive spondylometaphyseal dysplasia. Issue 1 (31st August 2021) - Turgut, Gozde Tutku; Güleç, Çağrı; Sarac Sivrikoz, Tugba; Kale, Hamdi; Karaman, Birsen; Nishimura, Gen; Altunoglu, Umut
Abstract: The lamin‐B receptor (LBR) encodes a dual‐functioning inner nuclear membrane protein essential for cholesterol biosynthesis and chromatin organization. LBR pathogenic variants cause distinct phenotypes due to the dual function of LBR, including Pelger–Huët anomaly (PHA), PHA with mild skeletal anomalies (PHASK; MIM# 618019), LBR‐related regressive type of spondylometaphyseal dysplasia (LBR‐R‐SMD), Greenberg dysplasia (MIM# 215140). We here report the first case with radiological manifestations of LBR‐R‐SMD in the fetal period, and milder skeletal findings in the similarly affected father. Direct sequencing of LBR revealed homozygous c.1534C>T (p.Arg512Trp) in exon 12 in both affected individuals. Our report further refines the early phenotype in LBR‐R‐SMD, and demonstrates that the p.Arg512Trp mutation is associated with PHA. We propose that LBR‐R‐SMD should be considered as a differential diagnosis in pregnancies with sonographic evidence of short and bowed tubular bones with narrow thorax. Evaluating peripheral blood smears of expectant parents for the presence of PHA may lead to a clinical diagnosis, allowing for comprehensive prenatal genetic counseling.